Achieving high HPV vaccine completion rates in a pediatric clinic population - Abbey B. Berenson; Richard Rupp; Erin E. Dinehart; Leslie E. Cofie; Yong-Fang Kuo; Jacqueline M. Hirth (Taylor & Francis Group, 2019)
Objective: To evaluate the efficacy of an intervention utilizing patient navigators (PNs) to 1) educate families on human papillomavirus (HPV) vaccination in a clinic setting and 2) provide personalized reminders for follow-up. Method: Families with 9-17 year-old children who had no record of completing the HPV vaccination series receiving primary or specialty care in 3 pediatric clinics were approached by PNs between February 1, 2015 and August 31, 2016. Demographic characteristics, visit type, preferred contact method, rates and correlates of completion, and appointments missed were analyzed. In addition, qualitative interviews of 21 providers and PNs assessed their perceptions of the program. Results: 1,391 adolescents were identified out of 2,162 patients approached as unvaccinated or partially vaccinated prior starters; among the unvaccinated, 930 received the 1st dose after being counseled by the PN (66.9%), either immediately or at a follow-up visit soon thereafter. This included 118 siblings of patients who did not have an appointment that day. Of initiators approached between 2/1/2015 and 8/31/2016, 93% (864/930) completed the series by 8/31/2017. No differences in series completion among initiators were observed by gender or race/ethnicity, but older patients (15-17 years old) were less likely to complete than 11-12 year olds. Of the 688 patients identified as prior starters, 85% completed the series through the program. Qualitative interviews demonstrated that providers felt the program addressed major barriers to HPV vaccination. Conclusion: Employing PNs dramatically increased HPV vaccine series completion among boys and girls with historically low HPV vaccination rates at pediatric clinics in Texas. Clinic providers felt this program addressed many barriers they observed prior to program implementation. This approach could markedly improve HPV vaccine series completion rates in the US.